Using Sequence Picture Technique to Increase the Students Writing Ability at First Grade of SMAN 1 Sungguminasa - Farisha Andi Baso (-)
Abstract The writing skills are complex and sometimes difficult to teach , The  difficulties are due  to weaknesses in grammar and vocabulary. Another problem, the students have a lot of ideas in their minds but they worry to start and even they don't know how to develop ideas. Uninteresting topic and unsuitable teaching techniques can influence students interest in writing English. To solve this problem, the English teacher should have to be more creative in choosing the material and techniques which can make the writing class more interesting, exciting and enjoyable. Materials are divided into two points they are visual and non visual material. Visual material offers, an attractive and stimulating framework for writing practice. One of the visual materials is picture. Picture is very suitable to be applied to the students of senior high school as a method writing skill. The objective of the research will find out the improvement students writing ability by using sequence picture and the interest of the students to use sequence picture at SMAN 1 Sungguminasa this research will use class action research that consisted two cycles the research population was the first grade of SMAN I Sungguminasa academic year 2015/2016the sample of this research consisted of 30 students. This will obtain the data by using writing test and questionnaire sheet. The reason why this research focuses on the sequence picture technique was that it will give the stimulate and motivate the students to study English special in writing skill. Beside that this technique will make the students become more attractive and interest in writing by using visual materialKey words: writing, sequence picture, interest.